2011
DOI: 10.2174/2211551x11201010072
|View full text |Cite
|
Sign up to set email alerts
|

Post-Translational Modifications of Natural Antimicrobial Peptides and Strategies for Peptide Engineering

Abstract: Natural antimicrobial peptides (AMPs) are gene-coded defense molecules discovered in all the three life domains: Eubacteria, Archaea, and Eukarya. The latter covers protists, fungi, plants, and animals. It is now recognized that amino acid composition, peptide sequence, and posttranslational modifications determine to a large extent the structure and function of AMPs. This article systematically describes post-translational modifications of natural AMPs annotated in the antimicrobial peptide database (http://a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…In general, this activity involves membrane interaction [3,4] and increasingly, it has been found that post-translational modifications (PTMs) play a role in optimising the efficacy and specificity of these mechanisms of action [5][6][7][8][9]. Most of the PTMs identified in AMPs are relatively infrequent in occurrence [6], typically the phosphorylation of residues [1,6,10] and the chiral inversion of residues to produce D-amino acids [11][12][13]. However, two PTMs have been found to be ubiquitous amongst AMPs of eukaryotes [6] of which the first is the oxidation of cysteine residues to form disulphide bridges [14].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…In general, this activity involves membrane interaction [3,4] and increasingly, it has been found that post-translational modifications (PTMs) play a role in optimising the efficacy and specificity of these mechanisms of action [5][6][7][8][9]. Most of the PTMs identified in AMPs are relatively infrequent in occurrence [6], typically the phosphorylation of residues [1,6,10] and the chiral inversion of residues to produce D-amino acids [11][12][13]. However, two PTMs have been found to be ubiquitous amongst AMPs of eukaryotes [6] of which the first is the oxidation of cysteine residues to form disulphide bridges [14].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the PTMs identified in AMPs are relatively infrequent in occurrence [6], typically the phosphorylation of residues [1,6,10] and the chiral inversion of residues to produce D-amino acids [11][12][13]. However, two PTMs have been found to be ubiquitous amongst AMPs of eukaryotes [6] of which the first is the oxidation of cysteine residues to form disulphide bridges [14]. It is generally accepted that disulphide bridges play a major architectural role in the antimicrobial action of AMPs [6], primarily by maintaining the amphiphilic topography of the molecules and thereby their ability to interact with target membranes and kill host cells [5,15].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…These two characteristics have been identified in several AFPs (Mura et al, 2016). Amidation of a peptide at its C-terminus has become of increasing interest, due to the removal of the negative charge, increasing antifungal activity and supporting resistance against proteases (Torrent, Andreu, Nogués, & Boix, 2011;Wang, 2014). Thus, the anti-Candida activity of P-113, a 12-amino acid fragment of Hst, is increased after amidation (Rothstein et al, 2001).…”
Section: Capping (C-and N-terminus Tagging)mentioning
confidence: 99%